Design of Augmented Reality-Based Learning Media Using the TPACK Framework for Visualizing Graph Concepts in Discrete Mathematics - Ita Margaretta Br Tarigan (JCEIT: Journal of Computer Engineering and Information Technology, 2026)
The advancement of educational technology has created opportunities to develop innovative learning media that can enhance students’ understanding of complex and abstract concepts. In the Discrete Mathematics course, graph theory is considered one of the most challenging topics because it involves abstract relationships among vertices and edges, making concepts such as paths, cycles, trees, and spanning trees difficult for students to comprehend through conventional two-dimensional learning media. Therefore, this study aims to design an Augmented Reality (AR)-based learning media using the Technological Pedagogical Content Knowledge (TPACK) framework to support graph concept visualization in higher education. This study employed the Design and Development Research (DDR) method, consisting of problem identification, literature review, needs analysis, TPACK analysis, learning media design, system architecture design, user interface design, prototype development, and expert validation. The results produced a conceptual model of AR-based learning media that integrates technological, pedagogical, and content knowledge within a unified framework. The proposed design includes learning materials, AR-based three-dimensional graph visualization, practice exercises, evaluations, and user guidance features. The practical implication of this study is the provision of a systematic design framework that can serve as a reference for the development of AR-based educational applications in mathematics and computer science education. In conclusion, the integration of AR technology and the TPACK framework has the potential to facilitate the visualization of abstract graph concepts and support more interactive learning experiences. Further research is recommended to implement and evaluate the effectiveness of the proposed design in actual learning environments. REFERENCES Adipat, S. (2021). Developing Technological Pedagogical Content Knowledge (TPACK) through Technology-Enhanced Content and Language-Integrated Learning (T-CLIL) Instruction. Education and Information Technologies, 26(5), 6461–6477. https://doi.org/10.1007/s10639-021-10648-3 Belda-Medina, J., & Calvo-Ferrer, J. R. (2022). Integrating augmented reality in language learning: Pre-service teachers’ digital competence and attitudes through the TPACK framework. Education and Information Technologies, 27(9), 12123–12146. https://doi.org/10.1007/s10639-022-11123-3 Bödding, R., & Maier, G. W. (2026). Investigating the Modality and Signalling Principles in Immersive Augmented Reality Learning Environments. Journal of Computer Assisted Learning, 42(1), e70183. https://doi.org/10.1002/jcal.70183 Chen, H.-C., & Wong, L.-H. (2026). The MTA-TPACK Dynamic Collaboration Spiral: Making Pedagogical Thinking Visible in Human–AI Scientific Visualization for Sustainable Teacher Innovation. Sustainability, 18(6), 2718. https://doi.org/10.3390/su18062718 Choi, B., & Young, M. F. (2021). TPACK-L: Teachers’ pedagogical design thinking for the wise integration of technology. Technology, Pedagogy and Education, 30(2), 217–234. https://doi.org/10.1080/1475939X.2021.1906312 Irwanto, I. (2021). Research Trends in Technological Pedagogical Content Knowledge (TPACK): A Systematic Literature Review from 2010 to 2021. European Journal of Educational Research, volume–10–2021(volume–10–issue–4–october–2021), 2045–2054. https://doi.org/10.12973/eu-jer.10.4.2045 Kim, W., & Ok, M. W. (2021). A Comparison of Special and General Educators’Usage, Perceptions, and TPACK Levels Regarding the Use of Augmented and Virtual Reality. Journal of Special Education : Theory and Practice, 22(2), 15–44. https://doi.org/10.19049/JSPED.2021.22.2.02 Lachner, A., Fabian, A., Franke, U., Preiß, J., Jacob, L., Führer, C., Küchler, U., Paravicini, W., Randler, C., & Thomas, P. (2021). Fostering pre-service teachers’ technological pedagogical content knowledge (TPACK): A quasi-experimental field study. Computers & Education, 174, 104304. https://doi.org/10.1016/j.compedu.2021.104304 Nilsson, P. (2024). From PCK to TPACK - Supporting student teachers’ reflections and use of digital technologies in science teaching. Research in Science & Technological Education, 42(3), 553–577. https://doi.org/10.1080/02635143.2022.2131759 Nusroh, H., Khalif, M. A., & Saputri, A. A. (2022). Developing Physics Learning Media Based on Augmented Reality to Improve Students’ Critical Thinking Skills. Physics Education Research Journal, 4(1), 23–28. https://doi.org/10.21580/perj.2022.4.1.10912 Prihantini, P., Rukmini, A., Mahardhani, A. J., & Mustika, A. (2026). Mapping the Progress of Technological Pedagogical and Content Knowledge Research: Bibliometric Analysis. Jurnal Pembelajaran, Bimbingan, Dan Pengelolaan Pendidikan, 6(2), 12. https://doi.org/10.17977/um065.v6.i2.2026.12 Putri, N. P. D. M., Suharta, I. G. P., & Astawa, I. W. P. (2022). DEVELOPMENT OF AUGMENTED REALITY BASED GEOMETRY LEARNING MEDIA ORIENTED TO BALINESE ARCHITECTURE TO IMPROVE ABILITY STUDENT MATHEMATICS SPATIAL. International Journal of Engineering Technologies and Management Research, 9(10), 26–42. https://doi.org/10.29121/ijetmr.v9.i10.2022.1183 Santos, J. M., & Castro, R. D. R. (2021). Technological Pedagogical content knowledge (TPACK) in action: Application of learning in the classroom by pre-service teachers (PST). Social Sciences & Humanities Open, 3(1), 100110. https://doi.org/10.1016/j.ssaho.2021.100110 Schwajda, D., Friedl, J., Pointecker, F., Jetter, H.-C., & Anthes, C. (2023). Transforming graph data visualisations from 2D displays into augmented reality 3D space: A quantitative study. Frontiers in Virtual Reality, 4, 1155628. https://doi.org/10.3389/frvir.2023.1155628 Sriadhi, S., Hamid, A., Sitompul, H., & Restu, R. (2022). Effectiveness of Augmented Reality-Based Learning Media for Engineering-Physics Teaching. International Journal of Emerging Technologies in Learning (iJET), 17(05), 281–293. https://doi.org/10.3991/ijet.v17i05.28613 Tarigan, I. M. B. (2026). Development of a Student-Centered Digital Mathematics Learning Prototype Using the ADDIE Model to Improve Conceptual Understanding. Journal of Computer Engineering and Information Technology, 2(1). Tarigan, I. M., Simanjorang, M. M., & Siagian, P. (2022). Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Perbedaan Gender di SMP N 1 Kuta Buluh. Jurnal Cendekia : Jurnal Pendidikan Matematika, 6(3), 2984–2998. https://doi.org/10.31004/cendekia.v6i3.1791 Yang, L., Susanti, W., Hajjah, A., Marlim, Y. N., & Tendra, G. (2022). Perancangan Media Pembelajaran Matematika Menggunakan Teknologi Augmented Reality. Edukasi: Jurnal Pendidikan, 20(1), 122–136. https://doi.org/10.31571/edukasi.v20i1.3830 Yanuarto, W. N., & Iqbal, A. M. (2022). The Augmented Reality Learning Media to Improve Mathematical Spatial Ability in Geometry Concept. Edumatica : Jurnal Pendidikan Matematika, 12(01), 30–40. https://doi.org/10.22437/edumatica.v12i01.17615 Yeh, Y.-F., Chan, K. K. H., & Hsu, Y.-S. (2021). Toward a framework that connects individual TPACK and collective TPACK: A systematic review of TPACK studies investigating teacher collaborative discourse in the learning by design process. Computers & Education, 171, 104238. https://doi.org/10.1016/j.compedu.2021.104238